2023
DOI: 10.3390/su15064781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Competent Human Capital, Strategic Flexibility and Turbulent Environment on Sustainable Performance of SMEs in Manufacturing Industries in Palestine

Abstract: The contribution of Small and Medium-Sized Enterprises (SMEs) to economic prosperity and expansion is widely acknowledged worldwide. However, the empirical evidence in the literature on enhancing sustainable performance in manufacturing industries, specifically SMEs in developing countries living under constant unstable economic and political environments such as Palestine, is still insufficient. Referring to the theory of Triple Bottom Line (TBL), Contingency Theory (CT), Natural Resource Based View (NRBV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 115 publications
0
12
0
Order By: Relevance
“…Therefore, the coping strategies obtained based on the evaluation results of supply chain resilience can only play a more obvious role in the short term. (3) The conclusions of this study are somewhat homogeneous and lack comparative studies for other industries.…”
Section: Research Limitations and Perspectivesmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the coping strategies obtained based on the evaluation results of supply chain resilience can only play a more obvious role in the short term. (3) The conclusions of this study are somewhat homogeneous and lack comparative studies for other industries.…”
Section: Research Limitations and Perspectivesmentioning
confidence: 85%
“…There-fore it is necessary to create a low-carbon supply chain system to promote the development of low-carbon enterprises [ 2 ]. However, in recent years, as the risk of global uncertainty increases, unexpected events such as trade protectionism and geopolitical conflicts occur frequently [ 3 ]. Enterprises face a range of problems in today’s market environment, such as reduced demand, insufficient supply of raw materials, production constraints, backlogs of finished products, and logistical disruptions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study found a positive association between competence and sustainable performance, indicating that employees who feel competent are more likely to engage in sustainable practices. In line with this, Schröder et al, (2022); Dwikat et al, (2023) emphasized the role of management investing in developing employees' competences to make them more qualified for employing sustainable practices.…”
Section: Discussionmentioning
confidence: 96%
“…Shamsuzzoha et al (2020) [ 14 ] examine the role of top managers’ human capital and other exogenous determinants of the efficiency of manufacturing firms in Bangladesh by using heteroscedastic single-step stochastic frontier analysis. Dwikat et al (2023) [ 15 ] studied the impact of competent human capital on manufacturing development. They found that the increase in the level of innovative human capital inhibits, to some extent, the positive effect of external knowledge sourcing on high-quality innovation in manufacturing.…”
Section: Introductionmentioning
confidence: 99%